“Back to Africa with the Benin Art: Restitution and Re/Interpellation" - Conde, I. (IV CHAM International Conference Innovation, Invention and Memory in Africa, CHAM - Centre for the Humanities, Faculty of Social and Human Sciences, University Nova Lisbon, 17-20 July 2019, 2019)
Motivated by the report on the restitution of the African cultural heritage in France, published in 2018, this paper reflects on this agenda and also on the meaning of objects that circulate between countries and continents: with what past, narratives, appropriations and re-interpellation for creative and reflective dialogues on postcoloniality, art, and contemporary Africa. The report concretises the announcement of President Emanuel Macron, during his visit to Africa in 2017, to take the step of restitution; a historic step in France and, as expected, a model for other countries in Europe that keep their share of African heritage in custody or hostage of their museums, collections and the market. Hence, instead of unanimous applause, there was more expectation, apprehension, reaction face to the report that defends "times of return" for a "new relational ethic." It remains to be seen how the future, gradual and modulated, devolution of thousands of pieces to Africa, among which many of the unique and precious Art of Benin, are brought back. A case brought here so much by its actuality in the conjuncture, and beyond France, as well as by the history it transports and for which frame in the present.